Effect of plant extracts on the incidence of fungi and germination of soybeans (Glycine max) (Revista Sistemas de Producción Agroecológicos, 2018)
The treatment of soybean seeds (Glycine max) is aimed at controlling the agents that cause diseases that interfere in the productivity of the cultivated plants, since the percentage of damage caused by pests that can impede the initial good development of plants is significantly reduced, currently the control is carried out with chemical products, but these components affect the health, therefore less harmful alternatives for the effect are being considered. Therefore, the main objective was to determine whether plant extracts (PE) that contain secondary metabolites, could be converted into substances for the control of the fungi of the soybeans in storage, for which microorganisms were identified during the application of the treatments. The evaluated plant extracts were: T1: verbena (Verbena officinalis), T2: yopo (Anadenanthera peregrina), T3: chamber (Lantana camara) and T4: calendula (Calendula officinalis), compared with a control without treatment T5. The extracts were obtained in the laboratory, the fresh solid material of the plant was liquefied and 30% of its weight was added to water, making a 100% adjustment, the extracts were filtered and stored in a dark bottle stored in a conventional refrigerator. From previous observations, it was determined that the dilution to be used for this type of tests was 4 ml of plant extract with 10 ml of water per kilo of seed. For the diagnosis of pathogens, at eight days post-application, observations were made in triplicate on the treated seed; for germination tests napkins with five repetitions were used, the observations of the behavior of the seeds were made five and eight days after being sown. A completely randomized block design was used: five treatments, two blocks: seeds treated only with plant extract (PE) and seeds treated with chemical fungicides (CF) more PE, ANOVA and Duncan's multiple comparison tests were applied. The diagnosis that was made determining the storage fungi present during germination were: Aspergillus spp., Geotrichum spp., Mucor spp., Penicillium spp., and Rizophus spp. The extract of Verbena officinalis presented 94.33% of control over the fungi and the treatment with Anadenanthera peregrina presented 91%, with these two extracts the highest germination percentage was also observed at five and eight days.
Keywords: seeds; fungi; vegetable metabolites; soybeans